Experimental study of regur soil stabilization by using Non-metallic waste bottles. (2022) - Bharani, S.; Ramesh Kumar, G.; Ranjithkumar, J.; Boopathi, G.; Singaravelu, G.; Piradheep,
Abstract: Soil is one of the most important materials used in a variety of construction projects including earthwork and earth dams. The regur soil reveals high elastic characteristics and exhibits low shear strength. The elastic characteristics are due to the presence of a mineral named montmorillonite. So many different approaches are made to improve the soil characteristics stratum. Shredding of plastic wastes in different proportions exhibits high shear strength which enhances the engineering properties of the regur soil, so it increases the soil stabilization. The regur soil sample was collected and investigated the properties such as free swell test, standard proctor compaction, unconfined compressive strength. The non-metallic waste bottle has been shredded in to small pieces and it was replaced in the proportion of 0.25%, 0.5%. 0.75% and 1% by weight of soil. The laboratory tests are conducted to find the Geotechnical properties of the regur soil. By adding plastic wastes the behavior of the Engineering property is improved by conducting a California bearing ratio. From the investigation of this project, it is evident that the shear strength of the regur soil increase which ultimately increases its grade of usage for construction purposes.